FAKTOR PENDORONG DAN PENGHAMBAT DALAM KUALITAS PELAYANAN PUBLIK DI KANTOR DESA PENGARASAN KECAMATAN BANTARKAWUNG KABUPATEN BREBES - Emiraldo Win Pazqara; Johar Ma'muri Ma'muri (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The aim of writing this scientific work is to raise a discussion regarding the quality of public services at the Pengarasan Village Office, Bantarkawung District, Brebes Regency along with the driving and inhibiting factors. The method used in this research is descriptive qualitative with data collection through interviews, observation and documentation. From the results of the analysis, several things can be confirmed, including: first, from the tangible aspect, the service process at the Pengarasan Village Office is realized through easy and uncomplicated procedures, the availability of tools, including the discipline of officers in serving with a neat appearance (in uniform), arrive on time and serve based on queue number. However, this is inversely proportional to the less comfortable conditions in the service area. Second, from the aspect of reliability, officers are quite careful in providing services and refer to clear service standards, but on the other hand officers tend to lack the ability of officers to operate service support tools such as computers. Third, from the aspect of responsiveness, the service staff's response was quite good with the initiative to serve quickly and precisely, including the provision of a suggestion box. Fourth, from the assurance aspect, services are often free of charge, but on the other hand there tends to be problems in completing services on time. Fifth, from the empathy aspect, there is a priority scale for the interests of service users as a form of application of the service code of ethics, including the absence of discrimination in service. The supporting factors that influence the quality of public services at the Pengarasan Village Office are the readiness of human resources, modern equipment support, and an easily accessible location. Meanwhile, the inhibiting factors that influence the quality of public services at the Pengarasan Village Office are the lack of socialization to the community regarding service procedures, the lack of personnel on duty in the service section, including the lack of competence of service officers in utilizing service supporting infrastructure.